0
$\begingroup$

Given the following equation

$(1)\,\,\,\,x(x-1)y''+xy'-y=0$

Known that $y_{1}=x$

is a solution to his equation (one of many possible)

Now I need to solve the following equation

$(2)\,\,\,\,\,\,\,\,x(x-1)y''+xy'-y=x(x-1)^{2}$

This is a second order non homogenous differential equation with “non constant” coefficients, I would use a reduction of order for the “complementary homogenous” get the homogenous solution solution

$y_{h}=c_{1}(f_{1}(x))+c_{2}(f_{2}(x))$

and then use variation of variables to solver this one.

However is there asimpler way to do this ? can I reduce the order for the whole non-homogenous equation and get this solved ?

If yes(if I can reduce the order straight away, can you please explain when am I allowed to use it )

Thanks, :)

$\endgroup$
  • $\begingroup$ No, $y_1=x$ isn't solution of $x(x-1)y''+xy'+y=0$ $\endgroup$ – JJacquelin Aug 6 '16 at 15:34
  • $\begingroup$ @JJacquelin hey, corrected $\endgroup$ – Pavel Penshin Aug 6 '16 at 16:02
0
$\begingroup$

Since a particular solution $y_1(x)=x$ is known, the reduction of order is obtained with the change of function :

$$y(x)=xu(x) \quad\to\quad x^2(x-1)u''+x(3x-2)u'=x(x-1)^2$$ Let $v(x)=u'(x)$ $$x(x-1)v'+(3x-2)v=(x-1)^2$$ This is a first order linear non-homogeneous ODE.

I suppose that you can take it from here : First, solve the associated homogeneous ODE $x(x-1)v'+(3x-2)v=0$ which is of separable kind.

Second, solve the non-homogeneous ODE (method of variation of parameter).

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.